KINERJA PELAYANAN PUBLIK DAN KEBUTUHAN PENATAAN KELEMBAGAAN PENGELOLAAN WILAYAH PERBATASAN DI KALIMANTAN - Zakiyah, Siti (Jurnal Borneo Administrator, 2007)
Objectively, border area is indeed a backward district compared to areas outside the border areas. Moreover, this  condition has revealed some issues in the border areas such as chronic poverty, isolation, low human resource index, the absence of public service facilities, shortage of staple supplies, etc. It has to be admitted that up to this time the performance of both the central and local government in the public area as well as development of social economic (education, health, infrastructure, income increase, and purchasing power, etcetera) in the border area is still relatively very low. Various conditions exist in the border area as well as the low performance of the government in the public service area need to be anticipated by strengthening the role of the state, for example through structuring the organization/ institution. Structuring institution in the border area has ultimate goal i.e. to increase the quality of public service to the society in the border area and at the same time, it can stimulate the acceleration of economic social development equally.  Keywords: wilayah perbatasan, kinerja pelayanan, penataan kelembagaan